2013
DOI: 10.1007/s13365-013-0166-x
|View full text |Cite
|
Sign up to set email alerts
|

Substance P enhances HIV-1 infection in human fetal brain cell cultures expressing full-length neurokinin-1 receptor

Abstract: The associations between the neurokinin-1 receptor (NK-1R), substance P (SP), and HIV-1 were investigated in neurosphere-derived cultures of microglial-depleted human fetal brain cells (HFBC). Full-length NK-1R was identified in HFBC cultures. SP treatment of the HFBC increased intracellular calcium mobilization and decreased electrical impedance, both of which were blocked by the NK-1R antagonist aprepitant. SP treatment of HIV-1-infected HFBC up-regulated HIV-1 expression. These data show that human neural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The inability to trigger NK-1R decreases bacterial clearance and increases death rates in mouse models of infection (Verdrengh and Tarkowski, 2008). SP and/or NK-1R have been linked to disease caused by infectious agents (Douglas et al, 2001; Schwartz et al, 2013), autoimmune disorders (Mantyh et al, 1988), psychological disturbances (Fehder et al, 1997; Herpfer and Lieb, 2005; McLean, 2005; Ebner and Singewald, 2006; Carpenter et al, 2008), cancer (Esteban et al, 2006), atopic dermatitis (Toyoda et al, 2002), and cell proliferation (Goode et al, 2003). EF-Tu from S. aureus, S. epidermidis , and B. cereus has been shown to bind SP, with an associated increase in virulence and biofilm formation (Mijouin et al, 2013; N’Diaye et al, 2016).…”
Section: Moonlighting Proteins In Bacteriamentioning
confidence: 99%
“…The inability to trigger NK-1R decreases bacterial clearance and increases death rates in mouse models of infection (Verdrengh and Tarkowski, 2008). SP and/or NK-1R have been linked to disease caused by infectious agents (Douglas et al, 2001; Schwartz et al, 2013), autoimmune disorders (Mantyh et al, 1988), psychological disturbances (Fehder et al, 1997; Herpfer and Lieb, 2005; McLean, 2005; Ebner and Singewald, 2006; Carpenter et al, 2008), cancer (Esteban et al, 2006), atopic dermatitis (Toyoda et al, 2002), and cell proliferation (Goode et al, 2003). EF-Tu from S. aureus, S. epidermidis , and B. cereus has been shown to bind SP, with an associated increase in virulence and biofilm formation (Mijouin et al, 2013; N’Diaye et al, 2016).…”
Section: Moonlighting Proteins In Bacteriamentioning
confidence: 99%
“…Viral levels correlate with the amount of substance P released by immune cells and it has been suggested that this neuropeptide may facilitate viral replication by increasing the expression of receptors including CCR5 that are required for HIV infection of host cells (Bost, 2004a; Manak et al, 2010). In the CNS, human fetal brain cells have been shown to express NK-1R and interactions between this receptor and substance P appear to exacerbate HIV-1 infection (Schwartz et al, 2013). …”
Section: Evidence For the Involvement Of Substance P In Cns Disordersmentioning
confidence: 99%
“…The effect of SP on viruses that cause neurocognitive impairment, such as human immunodeficiency virus (HIV) has also been investigated. An in vitro study using human fetal brain cell cultures expressing full-length NK1R showed that SP enhances HIV-1 infection 27 . Likewise, in vivo studies demonstrated that SP drives macrophage polarization and inflammation in HIV patients with neurocognitive impairment [28][29][30] .…”
Section: Neuroinflammation and Substance Pmentioning
confidence: 99%